Prevalence and determinants of overweight and obesity in Thai adults: Results of the Second National Health Examination Survey - Aekplakorn W. (2014)
To describe the prevalence of overweight and obesity and examine their relationship with sociodemographic factors in Thai adults. Using data from a cross-sectional survey, the National Health Examination Survey 11 (NHES11), the authors examined the prevalence of overweight (BMI > 25 kg/m2) and obesity (BMI ≥ 30 kg/m2) in 3,220 Thai adults aged 20-59 yr. Univariate analyses and Logistic regression models were used to examine the association of overweight and obesity with socio-demographic and behavioral risk factors. The overall age-adjusted prevalence of overweight and obesity were 28. 3% and 6.8% respectively, with a higher prevalence for women than for men (overweight: 33.9% vs 19.2% and obesity: 8.8% vs 3.5%). The prevalence of overweight and obesity was greater among older compared to younger people and among residents of urban (34.8% and 9.9%) compared to rural areas (26.4% and 5.9%). The prevalence of overweight and obesity varied by region in line with the level of economic development - Bangkok, Central, North, South and North-East. By using logistic regression analysis, overweight was associated with a number of characteristics as follows: age (per ten years increase) with adjusted Odds Ratio (OR) of 1.3; women 1.4; married 2.2; being a current smoker 0.4, and living in Bangkok and the central region 1.6 (compare to North-East). There was no clear difference in prevalence of overweight and obesity among education levels and type of occupation after controlling for other covariates. In conclusion, women of middle age, married, and living in Bangkok and the Central region, are at greater risk of overweight and obesity. Without effective lifestyle modification programs to curb these physiologic risk factors at population level, it is likely that related disease burden will ensue. Public health surveillance and intervention to modify the risk factors of excessive weight should be implemented.